2012
DOI: 10.13057/biodiv/d130204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plantations on plant species diversity in the Darabkola, Mazandaran Province, North of Iran

Abstract: Pourbabaei H, Asgari F, Reif A, Abedi R. 2012. Effect of plantations on plant species diversity in the Darabkola, Mazandaran Province,. In this study, the effect of plantations on plant species diversity was investigated in Darabkola, Mazandaran province, north of Iran. To conduct the study, a natural mixed forest, a broad-leaved plantation (Alnus subcordata-Acer velutinum) and a coniferous plantation (Cupressus sempervirens var. horizontalis-Pinus brutia) were selected. 35 sampling plots were taken in systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…All the same, diversity index was found consistently and significantly greater in native Quercus forests than exotic coniferous plantations forest. This result is in line with the findings of a number of research studies where the negative effects of afforestation on species diversity was highlighted (Andrés and Ojeda, 2002;Pourbabaei et al, 2012). Because species richness of vascular plants is affected by exotic coniferous species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All the same, diversity index was found consistently and significantly greater in native Quercus forests than exotic coniferous plantations forest. This result is in line with the findings of a number of research studies where the negative effects of afforestation on species diversity was highlighted (Andrés and Ojeda, 2002;Pourbabaei et al, 2012). Because species richness of vascular plants is affected by exotic coniferous species.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas some afforestation efforts are believed to harm ecosystem biodiversity and interfere with biodiversity conservation goals (Cao et al, 2009; Calvino-Cassela et al, 2012; Pourbabaei et al, 2012), a large number of studies in many countries has shown that the plantation of forests can provide habitat for a wide range of native forest plants, animals, and fungi and can support a diverse array of native understorey plants (Barbaro et al, 2005;Carnus et al, 2006;Brockerhoff et al, 2008;Juying et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Basal area was considered for dominancy and relative dominance (RD) calculated by: RD = (basal area of a species × 100) / total basal area of all species. The species diversity index was computed using the Shannon-Wiener information function (Krebs 1999;Sharma et al 2009;Abedi and Pourbabaei 2010;Pourbabaei et al 2012) as: H'=-Σn i /n log 2 n i /n, where: n i = denote to the SIV of a species and n= denote to the sum of total SIV of all species. The species evenness index was computed using the Pielou's evenness index (J) as: J = H' / ln S, where ln is Natural logarithm, S is the total species number in each plot.…”
Section: Discussionmentioning
confidence: 99%
“…We took a total of 30 sample plots (20 m × 20 m) selectively in the forest stand along an altitudinal range from 1300 m to 1800 m a.s.l. (Pourbabaei et al 2012;Zhang et al 2016). The forest stand was divided into five zones based on 100 m interval in the altitudinal gradient.…”
Section: Data Collection Sampling Of Understory Vegetationmentioning
confidence: 99%